Breastfeeding is associated with enhanced learning abilities in school-aged children - Johanna Inhyang Kim; Bung-Nyun Kim; Jae-Won Kim; Soon-Beom Hong; Min-Sup Shin; Hee Jeong Yoo; Soo-Churl Cho (BMC, 2017)
Abstract Objective The majority of studies on the associations between breastfeeding and cognitive functioning have focused on IQ, with only a few investigating learning skills, and none of the latter adjusting for maternal IQ. We examined the association between breastfeeding and learning abilities in school-aged children using a cross-sectional design. Methods We recruited 868 children, aged 8-11 years and parents completed the Learning Disability Evaluation Scale (LDES). Multivariable linear regression models were used and age, gender, area of residence, annual family income, maternal education, and maternal age at delivery, were included as covariates. Maternal IQ was added to further adjust for the effects of maternal cognitive ability. Path analysis was conducted to investigate the mediation effect of maternal IQ between breastfeeding and learning skills. Results Children who were ever-breastfed had higher learning quotient scores on the LDES (p = 0.001) as well as higher scores on subscales related to speaking (p = 0.001), reading (p = 0.005), writing (p = 0.004), spelling (p = 0.003), and mathematical calculation (p = 0.003) than the never-breastfed participants. All of these variables remained significant after adjusting for gestational and socioeconomic factors and for maternal IQ as covariates. The path analysis showed that breastfeeding had both indirect and direct effects on the learning quotient. Conclusions The results suggest that breastfeeding is positively associated with learning skills in school-aged children.